Educating Global Britain: Perils and Possibilities Promoting 'National' Values through Critical Global Citizenship Education. Issue 4 (2nd October 2018) - Bamber, Philip; Bullivant, Andrea; Clark, Alison; Lundie, David
ABSTRACT: Global citizenship education (GCE) within schools in England is increasingly being reoriented to address a statutory duty to promote fundamental British values (FBV). This multi-method study investigates the influence of critical GCE within initial teacher education in reshaping awareness, understanding and disposition towards FBV amongst beginning teachers. Findings highlight a tension between growing confidence and understanding of how to implement the FBV agenda and the development of autonomous dispositions of the kind demanded for the practice of critical GCE. Four teacher orientations towards FBV are developed and explored, demonstrating the role of practice-based learning for the cultivation of critical dispositions.